Rental Office di Kota Makassar Dengan Penekanan Net Zero Carbon - Gladis Anugrah Asmara; Muhammad Yusri Lukman; Andas Budy (Universitas Medan Area, 2026)
The economic growth of Makassar City reached 5.31% in 2023, driving an increase in the demand for office spaces. However, limited land availability and high property prices have led many companies to rent buildings that do not meet comfort, energy efficiency, and sustainability standards. On the other hand, Indonesia's commitment to the Paris Agreement requires the implementation of net-zero carbon principles in commercial buildings. This study aims to design a net-zero carbon-based rental office in Makassar City using a qualitative approach through field observations and literature reviews. The selected location is in Panambungan Village, Mariso Subdistrict, which meets the criteria of accessibility, infrastructure, and land availability. The building design optimizes energy efficiency through solar orientation, passive ventilation, a secondary skin (CLT timber and climbing plants), and a modular form with pilotis and atrium elements. The results show that this concept not only fulfills space requirements but also supports environmental sustainability by reducing the urban heat island effect and carbon emissions. This study contributes to the development of sustainable architecture while serving as a reference for future property development.